HUBUNGAN ANTARA TINGKAT PENGETAHUAN DAN SIKAP PERAWAT TERHADAP PELAKSANAAN PROGRAM INDONESIA SEHAT DENGAN PENDEKATAN KELUARGA DI PUSKESMAS KOTA PONTIANAK - Prianti, Lola; Maulana, Muhammad Ali; Fahdi, Faisal Kholid (Universitas Tanjungpura, 2021)
PIS PK is the main health development program that is carried out within the working area of the puskesmas. The level of knowledge and attitudes possessed by nurses may influence the implementation of PIS PK program. Objective:To analyze the relationship between the level of knowledge and attitudes of nurses towards the implementation of PIS PK program on public health center in Pontianak city. Method:Quantitative research with a cross sectional research design. The instrument used is a question related to the level of knowledge, attitudes and implementation of PIS PK. The sample was taken using a stratified random sampling technique and the number of research respondents was 48 people. Result : Statistics results with the chi square test obtained p value 0.131 which is greater than 0.05 (0.131 0.05) for the relationship between knowledge and implementation of PIS PK. Statistics results for the relationship between nurses' attitudes with the implementation of PIS PK chi square test obtained p value 0,000 which the value is less than 0.05 (0,000 0.05). Conclusion : There is no significant relationship between the level of knowledge and the implementation of PIS PK in the Pontianak city health center. However, there is a significant relationship between the level of knowledge and the implementation of PIS PK in the Pontianak city health center Keyword : Attitude Nurses, Knowledge Level, Pis Pk